2014
DOI: 10.1080/02571862.2014.907453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four Mozambican cowpea landraces for drought tolerance

Abstract: The southern part of Mozambique is vulnerable to drought affecting the country's food production requiring more drought-tolerant crops. Four local cowpea landraces, Massava nhassenje, Timbawene moteado, Namarua and Tete-2, which are currently widely used by local Mozambican farmers, were evaluated for their drought tolerance with the aim to identify the most drought-tolerant landrace and also a phenotypic marker easily applicable for drought tolerance selection under local Mozambican conditions. Above-and belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Mutants with bushy GH had reduced number of branches per plant. These characters are indicated to be associated with some physiological properties of the plant including leaf senescence and indeterminate GH (Hall, 2004; Martins et al, 2014). It is reported that characteristics altered through mutation breeding can be combined through the conventional breeding to improve crop performance and drought adaptation (Ehlers and Hall, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Mutants with bushy GH had reduced number of branches per plant. These characters are indicated to be associated with some physiological properties of the plant including leaf senescence and indeterminate GH (Hall, 2004; Martins et al, 2014). It is reported that characteristics altered through mutation breeding can be combined through the conventional breeding to improve crop performance and drought adaptation (Ehlers and Hall, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Horn et al [ 4 ] isolated bushy growth habit mutants in γ-irradiated cowpea with fewer branches. Hall [ 56 ] and Martins et al [ 57 ] opined that bushy growth habits might be attributed to the plant’s altered physiological properties, including leaf senescence and indeterminate growth habit. Similarly, spreading growth habit mutants were isolated in cowpea treated with different doses of γ rays [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, cowpeas consumed regularly in diversified diets can assist children and pregnant and/or breastfeeding mothers in attaining nutritional security, or fighting micronutrient deficiencies such as vitamin A deficiency (Akpalu et al, 2014;Owade et al, 2020). The high protein content of cowpea is derived from its association with symbiotic root nitrogen-fixing microbes which ultimately also contributes to sustainable agriculture and restoration of soil health (Akpalu et al, 2014;Martins et al, 2014;Horn et al, 2016). Reports of post-harvest losses of cowpea grain and leaves, however, are high, namely due to challenges in handling, distribution, and nutritional quality deterioration in storage (Owade et al, 2020).…”
Section: African Oil Palm (Elaeis Guineensis)mentioning
confidence: 99%